Statuens indre liv. En tolkning av Juan Muñoz' kunst - Aamold, Svein (Nordlit, 2010)
From the mid-1980's until his untimely death in 2001, the Spanish-born artistJuan Muñoz gained international acclaim for his sculptures, installations andmultimedia projects. This article discusses and interprets some of his figurativesculptural works, using concepts such as simulacrum, alienation, allegory, thestatue as an autonomous entity, and Walter Benjamin's notion of aura. Muñoz'ssculptures strongly invite us into illusionary settings and situations while at thesame time leaving us on the outside, as strangers in awkward situations. Thetheatrical, or performative, character of his larger installations, or tableauxvivants, such as Many Times (1999), questions not only our social andenvironmental relations, but also our individuality, as if we are confrontingmirrors that uncover our vulnerable subjectivity in highly disturbing ways.